2020
DOI: 10.1186/s40104-020-0429-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of dietary hemp seed oil to sows on fatty acid profiles, nutritional and immune status of piglets

Abstract: Background: The oil from industrial hemp seeds (Cannabis sativa) is an ideal source of stearidonic acid, which is a precursor fatty acid for the long-chained n-3 polyunsaturated fatty acids. These fatty acids are important for neonatal development, health and immunity. Hemp seed oil has been investigated for the influence on human health, but research on the impact in pig nutrition is scarce. The aim of our research was to study the effect of dietary hemp seed oil relative to soybean oil to lactating sows on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 43 publications
2
28
1
4
Order By: Relevance
“…An adequate passive transfer of maternal immunoglobulins to the newborn piglet is paramount as the porcine placenta act as a barrier for the transport of maternal immunoglobulins to the fetus [ 30 ]. As expected, the colostrum had a much higher content of IgG and IgM than milk as also shown in a recent study on sows from the same herd [ 31 ]. Interestingly, the sows provided the high antioxidant supplementation in the present study had an increased concentration of IgM in colostrum and milk.…”
Section: Discussionsupporting
confidence: 85%
“…An adequate passive transfer of maternal immunoglobulins to the newborn piglet is paramount as the porcine placenta act as a barrier for the transport of maternal immunoglobulins to the fetus [ 30 ]. As expected, the colostrum had a much higher content of IgG and IgM than milk as also shown in a recent study on sows from the same herd [ 31 ]. Interestingly, the sows provided the high antioxidant supplementation in the present study had an increased concentration of IgM in colostrum and milk.…”
Section: Discussionsupporting
confidence: 85%
“…However, with regard to offspring, these authors observed more positive effect on intestinal health and lower mortality of suckling piglets when dietary sodium butyrate was used for pregnant sows compared to the results observed for dietary MCFA or PUFA n-3. The experiment of Vodolazska and Lauridsen [4] confirmed that the maternal dietary fatty acid profile of oil influence the fatty acid profile in sows' colostrum and mature milk, blood plasma, and plasma of their progeny.…”
Section: Introductionmentioning
confidence: 81%
“…Similarly, the milk profile was increased in PUFA n-3 when sow were fed with diet containing the hemp seed oil during the late pregnancy and lactation, and piglets were able to convert these fatty acids obtained via the sow milk intake to C20:5 n-3 and C22:5 n-3. In addition, the oil type (hemp seed oil) in maternal diet positively increased the number of piglets born and decreased their mortality as well as the oil type affected the concentration of immunoglobins in blood of piglets [4].…”
Section: Effect Of Oils In Maternal Feeding On the Sows Reproductive mentioning
confidence: 99%
“…These authors studied some Italian edible hemp products (seeds, flour cake, and oil), and reported that cold-pressed HSO showed the PUFA content around 75%, followed by MUFA (13%) and SFA (about 10%). Lower values for SFA and MUFA, and higher values for PUFA were reported by other authors; for example, Ying et al (2018) (SFA 8.6%; MUFA 10.7%; PUFA 78.6%) for cold-pressed HSO purchased in Poland [ 21 ]; Vodolazska and Lauridsen (2020) for HSO provided by a Denmark manufacturer (SFA 9.4%; MUFA 11.3%; PUFA 78.5%) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%